2018
DOI: 10.1371/journal.pone.0196149
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical distribution of cerebral microbleeds and intracerebral hemorrhage in vertebrobasilar dolichoectasia

Abstract: ObjectivesVertebrobasilar dolichoectasia (VBD) is a dilatative arteriopathy associated with intracerebral hemorrhage. In the present study, we sought to evaluate the frequency and anatomical distribution of cerebral microbleeds (cMBs) and intracerebral hemorrhage (ICH) in VBD.MethodsFrom a MRI database 94 VBD patients were identified and analyzed with special emphasis on cMBs and ICH on T2*-weighted gradient echo images (GRE) in relation to the established diagnostic MRI criteria of VBD (diameter, height, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…CMBs are small (generally 2–10 mm), round or ovoid hypointensity lesions detected on T2*-gradient echo (GRE)/susceptibility-weighted imaging (SWI) and commonly found in patients with CSVD, including hypertensive arteriopathy (arteriolosclerosis) and cerebral amyloid angiopathy (CAA) [ 41 , 42 ]. Our results confirm the previously reported associations between CMBs and large vessel dilatative arteriopathy, IADE and its subset (VBD), in various populations including ischaemic stroke [ 32 , 33 , 43 ]. The degree of basilar artery tortuosity, BA dolichosis, was independently associated with deep CMBs (Odds ratio (OR) 4.14, P = 0.002) [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…CMBs are small (generally 2–10 mm), round or ovoid hypointensity lesions detected on T2*-gradient echo (GRE)/susceptibility-weighted imaging (SWI) and commonly found in patients with CSVD, including hypertensive arteriopathy (arteriolosclerosis) and cerebral amyloid angiopathy (CAA) [ 41 , 42 ]. Our results confirm the previously reported associations between CMBs and large vessel dilatative arteriopathy, IADE and its subset (VBD), in various populations including ischaemic stroke [ 32 , 33 , 43 ]. The degree of basilar artery tortuosity, BA dolichosis, was independently associated with deep CMBs (Odds ratio (OR) 4.14, P = 0.002) [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with prior observations of a higher frequency of pontine and cerebellar hemorrhage relative to other parts of the brainstem. 17 A study looking at cerebral microbleeds and ICH among 79 patients with vertebrobasilar dolichoectasia found that only two of the patients had microbleeds in the medulla oblongata and 6 of them had microbleeds in the pons. 17 All brainstem hemorrhage patients in our cohort were men, with a mean age of 58.5±13.1 years.…”
Section: Discussionmentioning
confidence: 99%
“…17 A study looking at cerebral microbleeds and ICH among 79 patients with vertebrobasilar dolichoectasia found that only two of the patients had microbleeds in the medulla oblongata and 6 of them had microbleeds in the pons. 17 All brainstem hemorrhage patients in our cohort were men, with a mean age of 58.5±13.1 years. Male gender and older age are considered risk factors for hemorrhagic stroke, including brainstem hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of CMBs and their territorial distribution depends on MRI gradient echo time (TE) sequence and according to their count the degree of severity was detected [5,35]. Dilatation and elongation of basilar artery was detected in brain MRA image [19,36].…”
Section: Discussionmentioning
confidence: 99%